Digital capacity in current education 4.0 development tendency - T. Lam, Hien; T. Nguyen, Lam; D.V Van, Phuong (Journal of Technical Education Science, 2021)
The development of science and technology has had a strong impact on the education environment recently. The integration of digital technologies and tools in teaching and learning activities and curricula have renovated the role of the schools, educators, and learners. Accordingly, learners are at the center of the learning process while educators and schools create suitable conditions to promote creativity and autonomy in the learners’ spirit. Both educators and learners need to have knowledge about digital capabilities which is one of the essential competencies in the 21st century